2015
DOI: 10.3727/108354214x14146846679367
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Information Channel on Information Source Selection: Students' Information Search

Abstract: A plethora of research studies has examined the effect of information channel and information source on information search behavior respectively but scant research that examined them together is located. This study conducted a factorial repeated-measures ANOVA to examine the interaction effect between information channel and information source on students' internship information search behavior. Empirical findings indicated a significant interaction effect in students' information use. That is, how informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Buckland (2013) 6 stated that modern trends and globalisation have changed the attitude and behavior of the younger generation, therefore there is a need to examine how youth seek cultural heritage information using a different channel. Personal characteristics act as a mediating effect in selecting information channels for seeking information 29 , effective selection of information channel influence on information source selection 30 . According to the study's findings, teenagers selected "elderly persons in the community" (mean=3.85) as the primary source of knowledge and rated first.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buckland (2013) 6 stated that modern trends and globalisation have changed the attitude and behavior of the younger generation, therefore there is a need to examine how youth seek cultural heritage information using a different channel. Personal characteristics act as a mediating effect in selecting information channels for seeking information 29 , effective selection of information channel influence on information source selection 30 . According to the study's findings, teenagers selected "elderly persons in the community" (mean=3.85) as the primary source of knowledge and rated first.…”
Section: Discussionmentioning
confidence: 99%
“…influence the choice in selecting information channels. Personal characteristics act as a moderator in selecting information channels for seeking information 29 , effective selection of information channels influences on the information source selection 30 . Thus, the incorporation of demographic characteristics is appropriate for this study.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the rise in use of mobile technology and the efficiency of mobile apps, a new phase of e-commerce has proliferated known as mobile commerce or "m-commerce", through which internet commercial transactions are being conducted via an alternative modus operandi -mobile devices, including smartphones (Malik et al, 2013). Under cost-benefit principles, it is suggested that consumers' make decisions utilizing information associated with lower search costs and more benefits (Lee et al, 2015). The benefits associated with the utilization of mobile technologies for consumers and businesses include, real-time accessibility of information at any location, personalization of the delivery of information and facilitation of immediate and interactive transactions (Karanasios et al, 2012).…”
Section: Lodging Industry Operating Performance and Profitabilitymentioning
confidence: 99%